PENGARUH BUDAYA ORGANISASI, MOTIVASI, DAN UPAH TERHADAP KINERJA KERJA KARYAWAN PT. SKELY INDONESIA - Emanuel Mantero (Journal of Accounting and Management, 2025)
This study aims to analyse the influence of organisational culture, motivation, and wages on employee performance at PT Skely Indonesia. The research method used is quantitative method with a sampling technique of 95 respondents. Data was collected through questionnaires and analysed using SPSS 23, including Validity Test, Reliability Test, Normality Test, Heteroscedasticity Test, Multicollinearity Test, and Multiple Regression Analysis. The results showed that: Organisational culture has a positive and significant effect on employee performance (p-value = 0.004). Motivation has a positive and significant effect on employee performance (p-value = 0.045). Wages have a positive and significant effect on employee performance (p-value = 0.000). Simultaneously, organisational culture, motivation, and wages have a significant effect on employee performance with an R-Square of 74.3%, which means that the three variables are able to explain 74.3% of variations in employee performance, while the rest is influenced by other factors not examined in this study. Thus, companies are expected to improve a positive organisational culture, provide effective motivation, and establish a fair wage system to optimally improve employee performance.